Activation of hepatic stellate cells by TGF alpha and collagen type I is mediated by oxidative stress through c-myb expression. - Lee, K S (1995)
Excessive production of collagen type I is a major contributor to hepatic fibrosis. Activated (myofibroblastic), but not quiescent, hepatic stellate cells (lipocytes) have a high level of collagen type I and alpha-smooth muscle actin expression. Therefore, stellate cell activation is a critical step in hepatic fibrosis. Here we show that quiescent stellate cells were activated by the generation of free radicals with ascorbate/FeSO4 and by malondialdehyde, a product of lipid peroxidation. In addition, stellate cell activation by collagen type I matrix and TGF alpha was blocked by antioxidants, such as d-alpha-tocopherol and butylated hydroxytoluene. Moreover, oxidative stress, TGF alpha and collagen type I markedly stimulated stellate cell entry into S-phase, NFkB activity, and c-myb expression, which were prevented by antioxidants. c-myb antisense oligonucleotide blocked the activation and proliferation of stellate cells induced by TGF alpha. Nuclear extracts from activated, but not from quiescent, stellate cells formed a complex with the critical promoter E box of the alpha-smooth muscle actin gene, which was disrupted by c-myb and NFkB65 antibodies, and competed by c-myb and NFkB cognate DNA. c-Myb expression was also stimulated in activated stellate cells in carbon tetrachloride-induced hepatic injury and fibrogenesis. This study indicates that oxidative stress plays an essential role, through the induction of c-myb and NFkB, on stellate cell activation.